The Role of table banking on socio- economic empowerment of women in Laikipia County - Gitonga, Purity Murimu (Strathmore University, 2018)
This study assessed the role of table banking on socio-economic empowerment of women in Laikipia County. The main objectives of the study were to measure the level of awareness of table banking in the county, determine the factors motivating women to borrow using table banking, examine the benefits of table banking as well as investigate the sustainability of table banking. The study was carried out in Laikipia County targeting women who currently belong and those who had left table banking groups. The study targeted 972 women who have enrolled with the recognized 21 table banking groups. Out of this number 822 is the estimated number of women who are still enrolled and 150 who are ex-members. For those in table banking, a sample of 269 was selected using snowballing technique, while census technique was adopted for 150 individuals who had left the groups. A questionnaire was used to collect primary data. Paired sample t-test statistic, at 95% confidence interval, was used to test whether there were statistically significant differences in socio-economic empowerment status between the women in table banking and women who had left table banking. The study found a strong positive relationship between the levels of awareness, motivation factors, benefits and sustainability of table banking and the socio-economic empowerment of women who were members of table banking. The paired sample t-test results showed that significant differences existed in the socio-economic empowerment status between the women in table banking and women who had left table banking. The study concluded that awareness of table banking was still low, motivation for participating in table banking included saving for school fees, raising business capital and sharing business ideas. Some of the key benefits included access to financing and socializing with other women. The sustainability of table banking was ensured by electing leaders with over three years’ experience in table banking, who attended regular loan management forums. The study recommended that, given that the main foundation of forming table banking groups was friendship, women who come together for social gatherings, family meetings, church activities and the like may be sensitized on how they can use those existing friendships to start table banking group. The study also recommends that there is need to motivate members to enroll others and to maintain their membership in order to enjoy the benefits that come with table banking. The study finally recommends that there is need for table banking officials to attend trainings on how to ensure the table banking is sustainable. There is also need to revise the current policies and constitutions guiding the groups in order to accommodate women of all economic status. The program should include aspects like how to increase membership outreach and ensure high retention rate of members.
Submitted in partial fulfillment of the requirements for the Degree of Master of Business Administration at Strathmore University